Incorporation of AgVO3 into Glass Ionomer Cement: Ionic Release - Mariana Pardi; Kaio Luca Gimenes Ribeiro; Manoela Borges e Souza Marques; Carla Regina Costa; Estephane Botan de Brito Silva; Marco Antônio Schiavon; Andréa Cândido dos Reis; César Penazzo Lepri; Denise Tornavoi de Castro (Pesquisa Brasileira em Odontopediatria e Clínica Integrada)
Objective: To evaluate the surface properties and ion release of a glass ionomer cement (GIC) incorporated with nanostructured silver vanadate (AgVO3). Material and Methods: Specimens were obtained with AgVO3 (1%, 2.5%, and 5%) and without nanomaterial. Charge dispersion was assessed by scanning electron microscopy (SEM) and energy dispersive X-ray spectroscopy (EDS). The release of silver (Ag+) and vanadium (V4+/V5+) was determined using inductively coupled plasma mass spectrometry (ICP-MS). The release of fluoride was determined using an ion-selective electrode. Data were analyzed by ANOVA and Bonferroni post-test (α=0.05). Results: Photomicrographs and EDS suggested the presence of AgVO3. The 2.5% and 5% groups showed a greater release of Ag+ (p<0.05). A greater release of V4+/V5+ was observed with 5% (p<0.05). There was a greater release of V4+/V5+ than Ag+ in the 2.5% (p=0.006) and 5% (p<0.001) groups. All groups showed a greater fluoride release on day 7 and a progressive decrease (p=0.004). On day 7, groups with 1% (p=0.036) and 2.5% (p=0.004) showed greater release than control. Conclusion: All concentration test altered the surface properties of GIC, with greater release of Ag+ and V4+ /V5+ in the group with 5%. In all groups, there was a greater release of fluoride on day 7 with a subsequent decrease. AgVO3 at concentrations of 1% and 2.5% favored fluoride release on day 7.